Efficacy and influencing factors analysis of SGLT2 inhibitors in treating heart failure following acute myocardial infarction - Du, Haiping; Xu, Hui; Bao, Jinwei (Frontiers in Pharmacology, 2025)
PurposeHeart failure (HF) following acute myocardial infarction (AMI) significantly impacts morbidity and mortality. Sodium-glucose co-transporter 2 (SGLT2) inhibitors, initially developed for type 2 diabetes mellitus, have shown cardiovascular benefits. This study evaluates the efficacy of SGLT2 inhibitors in treating HF post-AMI compared to conventional treatments.MethodsWe conducted a retrospective cohort study at our hospital from September 2022 to September 2024 involving 315 patients with HF post-AMI. Patients were categorized into a conventional treatment group (n = 140) and an SGLT2 inhibitor group (n = 175), with the latter further divided into effective (n = 154) and ineffective (n = 21) subgroups. Cardiac function was assessed pre- and post-treatment using echocardiography and serum biomarkers. Baseline characteristics and potential predictors of SGLT2 efficacy were also analyzed.ResultsThe SGLT2 group exhibited significant improvements in left ventricular ejection fraction (LVEF), decreased NT-proBNP, troponin I, and hs-CRP levels compared to the conventional group (P < 0.001). The overall effectiveness rate was 88.00% versus 75.71% in the conventional group (P = 0.004). Lower baseline LVEF and higher NT-proBNP levels were significant predictors of better outcomes. Notably, adverse reactions such as angina were reduced in the SGLT2 group.ConclusionSGLT2 inhibitors were associated with enhanced cardiac function and reduce cardiac stress markers in HF patients post-AMI, suggesting their potential as an adjunctive therapy. Lower baseline LVEF and higher NT-proBNP levels may predict better response, suggesting their utility in personalized treatment strategies. This was a retrospective single-center study, and further prospective trials are needed to confirm these findings.